Hyaluronan and Collagen in Human Hypertrophic Cardiomyopathy: A Morphological Analysis. (26th July 2012) - Hellström, Martin; Engström-Laurent, Anna; Mörner, Stellan; Johansson, Bengt
Abstract : Introduction . The hypertrophic cardiomyopathy (HCM) disease process is not only limited to cardiomyocyte abnormalities but also engages the extracellular matrix. Hyaluronan (HA) and its receptor CD44 are involved in cellular growth and tissue proliferation but have so far been less studied in myocardial hypertrophy. In HCM, collagens are abundant but their histological distribution and relation to hyaluronan have not been described. Material and Methods . Myocardial specimens from 5 patients with symptomatic left ventricular tract obstruction undergoing myectomy due to HCM were processed for histochemistry and immunohistochemistry. Results . HA staining was more intense in HCM patients. The histological distribution of HA was the same in patients and controls, that is, interstitial staining including the space between cardiomyocytes, in fibrous septa, and in the adventitia of intramyocardial blood vessels. CD44 was not detected in the myocardium of patients or controls. Collagen I showed the same general localisation as HA but detailed distribution differed. Conclusions . This is the first study that describes the distribution of hyaluronan in human HCM. HA staining is more intense in HCM patients but without coexpression of its receptor CD44, at least not in the chronic phase of HCM. HA and collagen I have the same localisation.